A study on the correlation of gastrointestinal bleeding and meteorological factors – is there a weather condition for GI bleeding? - Prechter, Florian; Bürger, Martin; Lehmann, Thomas; Stallmach, Andreas; Schmidt, Carsten (Zeitschrift für Gastroenterologie, 2019)
Aim We tried to identify a possible correlation between meteorological factors and the frequency of gastrointestinal bleeding (GIB).Methods We analyzed all endoscopic examinations performed because of suspected GIB from 2013 to 2016 at Jena University Hospital, Germany. Confirmed bleeding events were correlated with local meteorological data and meteorological season using multivariate analysis.Results Among a total of 35 522 examinations, we identified 5310 endoscopies performed for suspected GIB (61.5 % upper, 38.5 % lower endoscopies). In 35.5 %, GIB could be ascertained, gastroduodenal ulcers being the most frequent bleeding source. Of bleedings, 46.7 % merited an endoscopic intervention. Multivariate analysis did not show a correlation between meteorological factors and the total number of bleeding events. In subgroup analysis, lower ambient temperatures as well as pronounced changes in daily temperature were significantly associated with a higher rate of variceal hemorrhage (incidence rate ratio [IRR]: 0.961 for higher minimum temperature, p = 0.019; IRR: 1.119 per degree temperature change, p = 0.021), whereas ulcerative bleeding was associated with changes in air pressure (IRR: 1.031 per hPa, p = 0.010).Conclusions Our study does not support the correlation of meteorological conditions with the frequency of GIB per se. However, we found a statistically significant increase of variceal bleeding episodes along with lower ambient temperatures and pronounced changes in daily temperature. Patients at risk for variceal hemorrhage should be advised to avoid exposure to low temperatures, whenever possible. Ulcerative bleeding was significantly associated with changes in air pressure.
Keywords: gastrointestinal hemorrhage; weather condition; meteorological factors; esophageal varices